KESAMAAN BUNYI BAHASA TULIS AKSARA LAMPUNG DAN AKSARA BATAK TOBA SUMATERA UTARA - Umi Kholidah; Dwi Fitriyani; Rohmah Tussoleha; Laura Monica (Bahtera Indonesia, 2023)
This study aims to describe the similarities in the sounds of written language in the Lampung script and the Toba Batak script of North Sumatra. The method used is descriptive qualitative method. The results of the study show that there are several similarities in the sounds of written language in the Lampung script and the Toba Batak script. All the main letters of the Lampung script and Toba Batak script end in [a]. The entire sound of the Toba Batak script is exactly the same as the sound of the Lampung script, only the sound [ka] in the Lampung script is not found in the Toba Batak script. The sound of the children of this letter in the Batak Toba script [ng] and [h] has the same sound as the children of the Lampung script, namely Tekehole [ng] and Kelengiah [ah]. In conclusion, the similarities in the sound of written language in the Lampung script and the Toba Batak script can be seen from a historical background that both originate from India. The Lampung script comes from the Devanagari script and the Toba Batak script from Brahmi writing (India). Therefore, the Lampung script and the Toba Batak script have many similarities in the sound of their languages.